게임기반 학습법이 간호대학생의 학습몰입, 학습만족도 및 팀워크에 미치는 효과 - 강경림; Kang Kyoungrim; 이상화; Lee Sang-hwa; 박교연; Park Kyo-yeon (글로벌 건강과 간호, 2025)
Purpose: This study examined the effects of applying game-based learning to normal childbirth nursing in a women's health nursing class on nursing students' learning engagement, learning satisfaction, and teamwork. Methods: A single-group pre- and post-test design was adopted. The subjects were 77 college students enrolled in the Department of Nursing at a university in City G, who were taking women's health nursing courses. The study instrument was a self-report questionnaire consisting of 37 items: two questions on general characteristics, 17 on learning engagement, 10 on learning satisfaction, and eight on teamwork. The subjects studied normal childbirth nursing for six weeks, followed by a game-based learning session in the seventh week. Results: Learning engagement (t=-2.01, p=.048), learning satisfaction (t=-5.41, p<.001), and teamwork (t=-3.59, p=.001) significantly increased after the implementation of game-based learning. Conclusion: This study confirmed that game-based learning for normal childbirth nursing exerted a positive effect on learning engagement, learning satisfaction, and teamwork for nursing students. Therefore, we suggest that such learning be actively developed so that it can be used in various nursing classes and its effects confirmed in various variables.